Kekerasan dan Mikrostruktur Al-Si Pada Sebuah Produk Tuangan dengan Tebal Berlainan - Prayitno, Dody; Rajasagaran, Rajasagaran (MESIN, 2007)
Hardness of Microstructures of The As Cast (Al-Si) with different thickness, The aim of theresearch is to investigate effect ofthickness of casting on thehardness and microstructure ofaluminumsilicon.Theresearch started by melting the Al-I0%Si at 750 "C. A wood pattern which varies in thicknesswas used in the making a sandmould. The molten metal was poured into the sandmould. Finally the ascastis cut, grinded andpolishedfor metallographic andhardness testing. An etching solution, HCl I %was usedfor metallographic and the sampleswereobserved under a SEMmachine. The Vickers hardnesstesting machine is used. The experimental researches show that reducing in thickness of casting willreduce silicon-eutectic size and increase the hardness.